Generative Diffusion Model-Driven Autonomous Systems: A Framework for Scalable Engineering Management - Neha Boloor (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The rapid evolution of artificial intelligence has catalyzed the emergence of autonomous systems capable of transforming engineering management. This study introduces a comprehensive framework integrating generative diffusion models into autonomous decision-making systems to enhance scalability, adaptability, and performance in dynamic engineering environments. The proposed model simulates high-fidelity operational scenarios, enabling reinforcement learning agents to train on diverse and realistic inputs. Experimental evaluations across energy load balancing, predictive maintenance, and resource allocation tasks revealed significant improvements in task completion speed, policy convergence, and adaptability. Statistical analyses, including t-tests, ANOVA, and clustering validation, confirm the effectiveness of the framework under uncertainty and varying system loads. Visualizations of diffusion processes and heatmaps of decision latency further support the system’s robustness and foresight. The results demonstrate that generative diffusion model-driven autonomy presents a scalable and intelligent solution for managing complex engineering operations, laying the groundwork for broader deployment in real-world applications.